Type D personality, social support and depression in patients with diabetes: a structural equation model - Lin, Yingjie; Xu, Na; Sui, Yi; Zou, Qiangwei; Zhang, Jinglan; Zhao, Li (Frontiers in Endocrinology, 2026)
ObjectiveTo investigate the current status of depression among patients with diabetes and the influencing factors, and to analyze the relationship between Type D personality, social support and depression.MethodsThis study is a multi-center cross-sectional study. Using the cluster random sampling method, 1000 patients with diabetes were randomly selected from 6 tertiary hospitals in Shenyang from June to August 2024. Data was collected using a questionnaire consisting of the Type D Personality Scale, Perceived Social Support Scale, and Self-rating Depression Scale. Statistical analysis was conducted using SPSS 22.0 and AMOS 24.0. χ2 test, logistic regression model, and decision tree model were employed to investigate the influencing factors of depression in patients with diabetes. The predictive performance of the logistic regression and decision tree models was compared using the ROC curve. Pearson correlation analysis was conducted to examine the correlations between key variables. Additionally, a structural equation model was constructed to explore the relationships among type D personality, social support, and depression, as well as to evaluate the mediating role of social support.ResultsThe ROC curve analysis indicated that the predictive performance of the logistic regression model was marginally superior to that of the decision tree model. Structural equation modeling demonstrated a significant negative association between social support and type D personality (β = -0.669, P < 0.01) as well as between social support and depression (β = -0.370, P < 0.01). When social support was treated as a mediating variable, the absolute value of the path coefficient between type D personality and depression decreased (β = 0.628, P < 0.01), suggesting a partial mediating effect.ConclusionThe prevalence of depression is higher in patients with diabetes, and type D personality in patients with diabetes increases their risk of developing depression, while social support plays a crucial role in maintaining and regulating mental health, which may reduce the risk of depression. Patients with diabetes who have a type D personality tendency may mediate the development of depression through their perception of social support. Therefore, interventions should aim to strengthen social support for these patients, improve their ability to utilize it, mitigate type D personality traits, and ultimately enhance their mental health.